Ketone body 3‐hydroxybutyrate mimics calorie restriction via the Nrf2 activator, fumarate, in the retina. Issue 1 (9th November 2017) - Izuta, Yusuke; Imada, Toshihiro; Hisamura, Ryuji; Oonishi, Erina; Nakamura, Shigeru; Inagaki, Emi; Ito, Masataka; Soga, Tomoyoshi; Tsubota, Kazuo
Summary: Calorie restriction (CR) being the most robust dietary intervention provides various health benefits. D‐3‐hydroxybutyrate (3HB), a major physiological ketone, has been proposed as an important endogenous molecule for CR. To investigate the role of 3HB in CR, we investigated potential shared mechanisms underlying increased retinal 3HB induced by CR and exogenously applied 3HB without CR to protect against ischemic retinal degeneration. The repeated elevation of retinal 3HB, with or without CR, suppressed retinal degeneration. Metabolomic analysis showed that the antioxidant pentose phosphate pathway and its limiting enzyme, glucose‐6‐phosphate dehydrogenase (G6PD), were concomitantly preserved. Importantly, the upregulation of nuclear factor erythroid 2 p45‐related factor 2 (Nrf2), a regulator of G6PD, and elevation of the tricarboxylic acid cycle's Nrf2 activator, fumarate, were also shared. Together, our findings suggest that CR provides retinal antioxidative defense by 3HB through the antioxidant Nrf2 pathway via modification of a tricarboxylic acid cycle intermediate during 3HB metabolism.